The poet and the fly : art, nature, god, mortality, and other elusive mysteries - Hudson, Bob, 1953- (Broadleaf Books, 2020)
In this revelatory book, Robert Hudson considers seven poets, each of whom wrote a provocative poem about a fly. Considering Emily Dickinson, William Blake, and several other poets, The Poet and the Fly brings together the poetry, the flies, and the poets' own lives to explore the imaginative, and often prophetic, insights that come from the startling combination of poetry and flies, the extraordinary and the ordinary.